Prevention and control of sewer system overflows MOP FD-17 (McGraw-Hill's AccessEngineering., 2012)
"The purpose of this manual of practice is to provide the information necessary to help managers and engineers understand and analyze an overflow problem (dry weather, CSO [combined sewer overflows], or SSO [sewer system overflows]) and provide guidance in finding the best strategies to reduce or eliminate it. It is also intended to serve as a planning guide in developing long-term control plans for CSOs and SSOs."